PROBLEMS OF THE DEINDUSTRIALIZATION OF THE SERBIAN ECONOMY - Stevanovic, Simo; Milanovic, Milan R.; Milacic, Srecko (Economics of Agriculture, 2013)
The paper analyzes the process of the industrialization, i.e. deindustrialization of the Serbian economy in the time period after the Second World War until today. In the observed period, two contrary processes have been recorded. Until the beginning of the 1980s, the process of the accelerated industrialization of the economy was taking place. In the structure of the GDP, industry increased its share to around 44%. At the beginning of the 1990s, East European socialist countries and Serbia commenced the process of the transition of the economy and the economic system. In the starting phase of transition, all countries recorded a negative rate of their economic growth, a fall in the GDP and a reduction in the share of industry in the structure of GDP of the economy. Differently from the countries in which the negative tendencies of the economic growth were stopped in the mid-1990s, and which became the EU member countries in 2004 and 2007, the negative trend of the economic growth and the deindustrialization of the economy in Serbia continued during the first decade of the 21st century. In the previous twenty-year period, the GDP of the Serbian economy was reduced to 60% of the level of the 1990s. The 15.9% share of industry in the structure of the economy in 2009 is lower than the share of Yugoslavias industry immediately after the Second World War (around 20%).